The ACE2/Apelin Signaling, MicroRNAs, and Hypertension - Lai-Jiang Chen; Ran Xu; Hui-Min Yu; Qing Chang; Jiu-Chang Zhong (International Journal of Hypertension)
The renin-angiotensin aldosterone system (RAAS) plays a pivotal role in the development of hypertension. Angiotensin converting enzyme 2 (ACE2), which primarily metabolises angiotensin (Ang) II to generate the beneficial heptapeptide Ang-(1-7), serves as a negative regulator of the RAAS. Apelin is a second catalytic substrate for ACE2 and functions as an inotropic and cardiovascular protective peptide. The physiological effects of Apelin are exerted through binding to its receptor APJ, a seven-transmembrane G protein-coupled receptor that shares significant homology with the Ang II type 1 receptor (AT1R). The deregulation of microRNAs, a class of short and small noncoding RNAs, has been shown to involve cardiovascular remodeling and pathogenesis of hypertension via the activation of the Ang II/AT1R pathway. MicroRNAs are linked with modulation of the ACE2/Apelin signaling, which exhibits beneficial effects in the cardiovascular system and hypertension. The ACE2-coupled crosstalk among the RAAS, the Apelin system, and microRNAs provides an important mechanistic insight into hypertension. This paper focuses on what is known about the ACE2/Apelin signaling and its biological roles, paying particular attention to interactions and crosstalk among the ACE2/Apelin signaling, microRNAs, and hypertension, aiming to facilitate the exploitation of new therapeutic medicine to control hypertension.